W - 2 = -3....add 2 to both sides
w - 2 + 2 = -3 + 2...simplify
w = -1 <== ur solution
<span>Cancel <span>r2</span>
</span><span><span><span>(s4t)</span>/(</span><span>s<span>t3)</span></span></span>
2 <span>Use Quotient Rule: <span><span><span>xa/</span><span>xb</span></span>=<span>x^<span>a−b</span></span></span>
</span><span><span>s^<span>4−1</span></span><span>t^<span>1−3</span></span></span>
3 <span>Simplify <span>4−1</span> to 3
</span><span><span>s^3</span><span>t^<span>1−3</span></span></span>
4 <span>Simplify <span>1−3</span> to <span>−2</span>
</span><span><span>s^3</span><span>t^<span>−2</span></span></span>
5 <span>Use Negative Power Rule:<span><span>x^<span>−a</span></span>=<span>1/<span>xa</span></span></span>
</span><span><span>s^3</span>×<span>1/<span>t2</span></span></span>
6 <span>Simplify
</span><span><span>(s3)/(</span><span>t2)</span></span>
Done so the answer is a. then
Answer: what is ∠ ?
Step-by-step explanation:
Answer:
Step-by-step explanation:
6.